From Universal to Global - Harun Küçük (Journal for the History of Knowledge)
In this paper, I argue that the global history of knowledge may become an empirical substitute for philosophical epistemology. I present a fundamentally Braudelian vision for such a history, prioritizing long-term and large-scale analyses rather than simply focusing on travel and exchange. Finally, I argue that the material conditions that are best suited to the global history of knowledge may be found outside of the United States, where the professional reward structures and the existing structures of funding may not support collaborative work over longer periods of time.